Development of a DNA-based microarray for the detection of zoonotic pathogens in rodent species - Giles, Timothy Andrew (2015)
Emerging infectious diseases are, and have always been, an important threat to human health, animal health and the global economy. Emerging and re-emerging pathogens are opportunists, responding to changes in the host or environment. Therefore, diagnostic tests used for the detection of pathogens either of animal or human origin, must be just as adaptable in utilising new technology. In complex biological situations where multiple pathogens may be present or when using wildlife samples that may be rare or precious, DNA microarray technology is particularly valuable as hundreds or thousands of targets can be screened simultaneously in a single sample. This thesis investigated the potential of a DNA microarray as a screening tool for over 20 pathogens as part of the Novel Technologies for Surveillance of Emerging and Re-emerging Infections of Wildlife project (WildTech), an FP7 EU funded project (www.wildtechproject.com). The pathogens included zoonotic viruses, bacteria and parasites. Publicly available software was used for design of oligonucleotides for the array. Evaluation of the oligonucleotides was carried out using reference samples from a variety of sources. Different rodent species were screened including the principal commensal species Rattus rattus, Rattus norvegicus, and Mus musculus. Nucleic acid extracted from samples of liver, kidney and lung was screened for the presence of pathogens. The array successfully identified Leptospira and Seoul hantavirus positive samples from animals trapped in the United Kingdom, France and Canada. These results were confirmed using previously established methods. It is likely that, over the next few years, diagnostic microarrays will become relatively inexpensive research tools. Molecular testing for emerging pathogens is increasingly being utilised and use of this technology will result in timely, accurate and inexpensive diagnosis to enable effective control of these infectious diseases with important implications for human health. The data contributed here can aid in the steps required to design microarrays for screening purposes.